2007
DOI: 10.1007/bf03021706
|View full text |Cite
|
Sign up to set email alerts
|

Resuscitating patients with early severe sepsis: A Canadian multicentre observational study

Abstract: Background: Fluid resuscitation is a key factor in restoring hemodynamic stability and tissue perfusion in patients with severe sepsis. We sought to examine associations of the quantity and type of fluid administered in the first six hours after identification of severe sepsis and hospital mortality, intensive care unit (ICU) mortality, and organ failure. Methods:A retrospective, multicentre cohort study was undertaken at five Canadian tertiary care ICUs. We identified patients with severe sepsis admitted to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 28 publications
1
13
0
1
Order By: Relevance
“…Just as persistent and significant pruritus is now recognized as a deleterious consequence of starch administration,49 so too are the potential consequences for the kidney 48,50. Case reports, observational studies and randomized controlled trials involving various patient populations exposed to different HES fluids have inconsistently reported the occurrence of adverse kidney outcomes 4,13,14,16,17,48. Although each HES compound has unique pharmacokinetic properties that depend on the mean molecular weight, the degree of substitution and the C2:C6 ratio,51 it is unclear whether these differences affect clinically important outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Just as persistent and significant pruritus is now recognized as a deleterious consequence of starch administration,49 so too are the potential consequences for the kidney 48,50. Case reports, observational studies and randomized controlled trials involving various patient populations exposed to different HES fluids have inconsistently reported the occurrence of adverse kidney outcomes 4,13,14,16,17,48. Although each HES compound has unique pharmacokinetic properties that depend on the mean molecular weight, the degree of substitution and the C2:C6 ratio,51 it is unclear whether these differences affect clinically important outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This population may be especially vulnerable to the effects of resuscitation fluids known to adversely affect kidney function. The evidence about adverse renal outcomes associated with administration of HES from observational studies13-16 and randomized controlled trials7,17-19 is conflicting.…”
mentioning
confidence: 99%
“…52 In contraposition to these results, a Canadian study found a lesser incidence of renal failure in patients with sepsis resuscitated with crystalloids plus colloids (HES 200/0.5) than in those who received only crystalloids---though without differences in relation to mortality. 53 More recently, two clinical trials have evaluated HES of lesser molecular weight and lower molar substitution ratio (HES 130/0.4) in the resuscitation of critical patients or patients with severe sepsis and septic shock ( Table 2). The incidence of renal failure and the need for renal replacement therapy were greater in the patients who received HES than in those administered saline solution, though with no differences in mortality after 90 days (primary endpoint).…”
Section: Should We Use Hydroxyethyl Starch In Resuscitation Of the Crmentioning
confidence: 99%
“…Este efecto fue más acusado entre los pacientes que recibieron más de 20 ml/kg, si bien la tasa de fracaso renal y la necesidad de reemplazo renal fue también significativamente superior en los que recibieron < 20 ml/kg al compararlos con el grupo de Ringer Lactato 52 . En contraposición a estos resultados, un estudio canadiense halló una menor tasa de insuficiencia renal en pacientes con sepsis reanimados con cristaloides más coloides (HES 200/0,5) respecto a los que solo recibieron cristaloides, pero sin diferencias en la mortalidad 53 .…”
Section: ¿Debemos Emplear Hidroxietilalmidón En La Reanimación Del Paunclassified